DAMPAK PENGETAHUAN BERWIRAUSAHA DAN KEUNGGULAN BERSAING TERHADAP KEBERHASILAN USAHA SALON DI DAERAH SETIABUDI, KOTA MEDAN - Say Gumira; Sri Rezeki (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The rapid development of the beauty service industry has led to increased competition among salons, especially conventional salons. This situation requires business owners to have entrepreneurial knowledge and competitive advantages in order to achieve sustainable business success. This study aims to analyze the influence of entrepreneurial knowledge and competitive advantage on the success of conventional salons in the Setiabudi area, Medan City. The study uses a quantitative approach with a survey method. The study population consists of 33 owners of conventional class C and D salons, all of whom were sampled using a saturated sampling technique. Data collection was conducted using a questionnaire with a Likert scale, then analyzed using multiple linear regression with the help of SPSS software. The results showed that entrepreneurial knowledge had a positive and significant effect on business success. Competitive advantage was also proven to have a positive and significant effect on business success. Simultaneously, entrepreneurial knowledge and competitive advantage significantly influence the success of conventional salons. These findings emphasize the importance of improving entrepreneurial competence and competitive advantage strategies as efforts to increase the success and sustainability of conventional salons.